Analysis and Optimal Control Intervention Strategies of a Waterborne Disease Model: A Realistic Case Study - Obiora Cornelius Collins; Kevin Jan Duffy (Journal of Applied Mathematics)
A mathematical model is formulated that captures the essential dynamics of waterborne disease transmission under the assumption of a homogeneously mixed population. The important mathematical features of the model are determined and analysed. The model is extended by introducing control intervention strategies such as vaccination, treatment, and water purification. Mathematical analyses of the control model are used to determine the possible benefits of these control intervention strategies. Optimal control theory is utilized to determine how to reduce the spread of a disease with minimum cost. The model is validated using a cholera outbreak in Haiti.